A Methodology to Assess the Capacity of Neighborhoods to Accommodate Models of Active Aging Based on Sharing Housing. Málaga (Spain) as a Study Case. - Rosa-Jiménez, Carlos; Reyes-Corredera, Sergio Jesús; Mora Esteban, Rubén (My University, 2023)
The aging of the world population, especially in Europe, and the increase in the longevity of the elderly pose a major challenge in the habitability of cities. Neighborhoods for active aging constitute socio-spatial and social relation units that are the basis of active aging in the place. Recent literature has analyzed the ideal conditions of neighborhoods and the criteria for selecting homes for the residence of the elderly, but there is a significant lack of studies that analyze the theoretical capacity of neighborhoods to accommodate coexistence initiatives among older people on a city scale. The research selects quantifiable variables and, through the use of GIS, determines the most appropriate areas of Malaga (Spain), as a case study, to promote models of coexistence based on sharing housing. The investigation concludes that the first peripheries in flat areas are the most propitious spaces. The paper concludes by discussing the keys to research that can influence public policies.
Keywords: Vejez - Aspectos sociales; Arquitectura y ancianos; Active Aging; Neighborhood; Ageing in Place; GIS; Healthy Cities